Stiffness configuration of strongbacks to mitigate inter-story drift concentration in buildings. (15th November 2019) - Lin, Jui-Liang; Kek, Meng-Kwee; Tsai, Keh-Chyuan
Highlights: Development of a simplified numerical model for buildings with strongbacks. Parametric study of the stiffness configuration of strongbacks. Validation of the effectiveness of the stiffness configuration of strongbacks. Abstract: This paper examines the stiffness configuration of strongbacks to effectively mitigate inter-story drift concentration in buildings. This study first develops a simplified numerical model for simulating buildings with strongbacks. This simplified numerical model is capable of reflecting the various deformation types of the strongbacks and the original buildings, in which the distribution types of story stiffnesses and story masses are not limited. Through this simplified numerical model, a parametric analysis of the ratio of the stiffness of strongbacks to that of original buildings with various building heights and deformation types was conducted. In addition to the stated stiffness ratio, this study further explores the preferred stiffness distribution over the height of the strongbacks. The buildings with uniform distributions of story masses and story stiffnesses over the building heights rather than other specific distributions were considered in the parametric analysis. One nine-story steel moment-resisting frame building and one three-story reinforced concrete (RC) building with infilled RC walls were investigated to verify the effectiveness of the proposed stiffness configuration of strongbacks.